2021
DOI: 10.1007/s10071-020-01459-z
|View full text |Cite
|
Sign up to set email alerts
|

Do alternative reproductive tactics predict problem-solving performance in African striped mice?

Abstract: In changing environments, animals face unexpected problems to solve. Not all individuals in a population are equally able to solve new problems. It still remains unclear what factors (e.g., age, body condition) influence the propensity of problem-solving. We investigated variation in problem-solving performance among males following alternative reproductive tactics (ARTs). We studied a free-ranging population of the African striped mouse (Rhabdomys pumilio). Adult male striped mice can employ 3 ARTs: 1) domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Alternatively, male success in problemsolving could be related to their large size and better motor ability to open the device. However, a previous study using the same device showed that younger and smaller males striped mice solved the 20 task better than bigger males (Rochais et al, 2021). Finally, male striped mice showed faster attentional shifts in summer (Maille et al, 2015) which could have been related to faster problem-solving.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Alternatively, male success in problemsolving could be related to their large size and better motor ability to open the device. However, a previous study using the same device showed that younger and smaller males striped mice solved the 20 task better than bigger males (Rochais et al, 2021). Finally, male striped mice showed faster attentional shifts in summer (Maille et al, 2015) which could have been related to faster problem-solving.…”
Section: Discussionmentioning
confidence: 74%
“…The number of successful individuals was low for both seasons (summer: 31%; winter: 37%) suggesting that the task was difficult to solve, not ecologically relevant and/or conditions in a field lab were stressful. Nevertheless, a previous study based on the same protocol, showed that 57% of the tested striped mice were successful (Rochais et al, 2021) suggesting that striped mice are able to perform the task.The success rate itself did not differ seasonally, since the number of successful individuals and the number of lids opened did not differ between season. These results suggest that even when natural food availability was very low, problem-solving success was not affected.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The subject was video recorded using a go pro camera (AEE LYFE, S91B) mounted on the top of the box. Subjects were given a maximum of 5 min to complete the task whereafter those that did not complete the task were released 53 .
Figure 4 Graphical representation of part of the experimental protocol and device.
…”
Section: Methodsmentioning
confidence: 99%